Dragons of silk, flowers of gold a group of Liao-Dynasty textiles at the Abegg-Stiftung (Abegg-Stiftung, 2007)
Catalog of Liao-dynasty textiles in the collection of the Abegg-Stuftung, Riggisberg, Switzerland.